TECHNOLOGICAL PRACTICE IN FULL-TIME EDUCATION: MICROCLIMATIC INSTRUMENTATION WITH ARDUINO IN THE SOUTHERN AMAZON - Alves, Rodrigo Henrique Risso Aires; Pereira, Mariana Arinana Canuto; Araújo, Estephanie Guimarães; Martins, Wilson Ramos; da Silva, Diana Lima; dos Santos, Miquele Araújo; Oliveira, Ludimila Souza; Ponce, Ana Paula Silva (Seven Editora, 2026)
Considering that the teaching of climate dynamics often occurred in an abstract manner, disconnected from the students’ local reality within the full-time school schedule. This study aimed to report and analyze the construction of a low-cost automated microclimatic monitoring station, using the Arduino platform, as a tool for integrating ecological awareness and digital experimentation. To this end, a qualitative action research approach was conducted at the Centro Integrado de Atividades Complementares (CIAC), in the municipality of Humaitá, Amazonas, through the "Science Workshop: Environmental Education and Sustainability" with Elementary School students; the practical activity of electronic prototyping and programming logic allowed students to make technical decisions and directly recognize the characteristics of the school microclimate. Thus, it was observed that the collection and interpretation of real-time biometeorological data contextualized ecological concepts within the Amazonian reality, stimulating critical thinking and student protagonism, which led to the conclusion that the articulation between environmental education and technological practice qualified the full-time curriculum, transforming the school into an active space for socio-environmental diagnosis.